Clinical Application of Noninvasive Prenatal Testing for Sex Chromosome Aneuploidies in Central China - Zhao, Ganye; Dai, Peng; Wang, Conghui; Liu, Lina; Zhao, Xuechao; Kong, Xiangdong (Frontiers in Medicine, 2022)
Background The relatively high incidence and the clinical symptoms of sex chromosome aneuploidies (SCAs) make prenatal screening of SCAs an attractive option for pregnant women. However, limited studies have assessed the clinical performance of noninvasive prenatal testing (NIPT) for screening SCAs. This study was performed to evaluate the clinical performance of NIPT for SCAs in singleton pregnancies in central China. Methods Noninvasive prenatal testing was performed using next-generation sequencing. Standard Z-score analysis was used to identify fetal SCAs. NIPT-positive results were confirmed by invasive prenatal diagnosis (IPD). Results A total of 42,164 pregnant women with singleton pregnancies were recruited in this study. They were divided into the following five groups with different clinical indications: with ultrasound soft index abnormalities (9.23%, 3,892/42,164); with advanced maternal age (22.14%, 9,336/42,164); with high risk for maternal serum screening (MSS) (18.35%, 7,738/42,164); with an intermediate risk for MSS (26.6%, 11,215/42,164); and with low risk (23.68%, 9,983/42,164). In all, 223 women had a high risk for SCAs by NIPT with a positive rate of 0.53%. There was no significant difference associated with the five groups in the positive rate. Of all of the positive results, 89 were 45,X (39.91%), 38 were 47,XXX (17.04%), 31 were 46,XY,del(X) (13.90%), 50 were 47,XXY (22.42%,), and 15 were 47,XYY (6.73%). Finally, 147 participants (65.92%) chose to undergo IPD, and 47 cases were confirmed. The combined positive predictive value (PPV) of NIPT for SCA was 31.97% (47/147). PPV was high for 47,XYY (100%, 11/11), moderate for 47,XXX (42.86%, 9/21) and 47,XXY (45.45%, 15/33), but low for 45,X (16.13%, 10/62) and 46,XY,del(X) (10%, 2/20). The termination rates of Turner syndrome and 47,XXY syndrome were higher than 47,XXX and 47,XYY syndromes. Conclusion In this relatively large cohort, we evaluated the value of NIPT for SCAs. Our data showed that with informed consent and subsequent professional genetical consulting, NIPT can be a useful method to screen SCAs.